INTRASPECIFIC VARIABILITY OF THE Sus1 SUCROSE SYNTHASE GENE IN Pisum sativum ACCESSIONS - E. A. Dyachenko; M. A. Slugina (Вавиловский журнал генетики и селекции)
The pea Pisum sativum is widely cultivated in Russia as well as over the world. Pea productivity depends on the ability of the pea plant to get into a symbiosis with nodule bacteria. It was previously shown that the strength of the symbiotic activity depends on the activity of plant sucrose cleavage enzymes. Sucrose synthase Sus1 is one of the most important enzymes involved in carbohydrate metabolism. Sucrose synthase cleaves sucrose into UDP-glucose and fructose. This paper is devoted to characterization of Sus1 gene intraspecific variability in 14 Pisum sativum accessions. The length of the identified Sus1 gene varied from 3514 bp to 3532 bp. All identified genes had a similar structure and contained 13 exons and 12 introns. According to their structure, they were assigned to the SUS1-group of dicotyledonous plants. In nucleotide sequences, 125 SNPs were identified. In addition to SNPs, intron sequences contained six indels, thus their length varied from 1093 bp to 1111 bp. The most variable was the intron III. In coding sequences, 47 SNPs were found, wherein the most variable was the exon II. 16 exon SNPs led to amino acid substitutions. Six of them were deleterious and may potentially influence protein folding and stability. All the conservative motifs and active sites were detected in the translated amino acid sequences. It was shown that their sequences were invariable in all the tested accessions. Computational analysis of the amino acid sequences has predicted Sus1 tertiary structure. The protein is a tetramer and each subunit in its turn consists of three domains. The phylogenetic analysis using identified Pisum Sus1 sequences and homologous sucrose synthase genes revealed that the Sus1 and Sus3 genes are closer to each other than to Sus2. It was also proposed that the sucrose synthase family genes had diverged before legumes split into species.